Case Study of Intelligent Children Through The Application of Bruner's Theory on The Operations addition and subtraction of Integers for the Students SMPKH YDKW Tangerang - Tiesa Rahma Azzura (Universitas Negeri Makassar, 2021)
This study aims to find out how to add and subtract mentally retarded children through the application of Bruner's theory at a moderate level in mathematics learning, especially in addition and subtraction operations of integers through the application of Bruner's Theory. This type of research is a qualitative research with case study method. The research subjects were 4 mentally retarded children who were in class VII SMPKH YDKW 01 Tangerang. Based on the results of research and structured interviews, it shows that the operation of addition and subtraction on integers through symbolic means through the application of Bruner's theory shows that 25% meet the minimum completeness criteria of the predetermined criteria